A Structure‐Activity Investigation on Modified Analogues of an Argininocalixarene Based Non‐viral Gene Vector. Issue 29 (20th May 2021) - Lomazzi, Michela; Franceschi, Valentina; Bagnacani, Valentina; Vezzoni, Carlo Alberto; Donofrio, Gaetano; Casnati, Alessandro; Sansone, Francesco
Abstract: The tetra‐L‐arginino‐tetrahexyloxycalix[4]arene 1 has shown extraordinary abilities to compact and internalize different types of Nucleid Acid cargos (DNA, microRNA, PNA) into cells even known to be transfected with great difficulties by commercial non‐viral gene delivery systems. This activity, accompanied by negligible toxicity, makes this calixarene a rather promising prototype of vector for Gene Therapy. In this study we report how small structural changes like i) the lower rim alkyl substituents, ii) the type of the terminal cationic headgroups (guanidinium or primary ammonium), iii) the length of the linker between the macrocycle and the terminal cationic headgroup, iv) the presence/absence of the basic α‐amino group of Arg, and v) the stereochemistry (L or D) of Arg, might affect the ability of the novel calixarene vectors to compact DNA and to deliver its cargo into the cells. Abstract : A series of eight novel calix[4]arene‐cone amphiphiles bearing different types and numbers of cationic headgroups at the upper rim and different alkyl chains at the lower rim were synthesized and studied in pDNA binding and cell transfection in order to dissect the role of each of these structural elements on gene delivery properties of this promising class of non‐viral vectors.